Front-Line Human Resource Time-Use for Early Infant HIV Diagnosis: A Comparative Time-Motion Study at Centralized and Point-of-Care Health Facilities in Zimbabwe. (1st July 2020) - Adetunji, Oluwarantimi; Mukherjee, Sushant; Sacks, Emma; Ciaranello, Andrea; Chadambuka, Addmore; Mafaune, Haurovi; McCann, Nicole; Cohn, Jennifer
Abstract : Background: Point-of-care (POC) assays for early infant diagnosis of HIV (EID) increase access to testing, shorten time to results, and expedite initiation of antiretroviral therapy when compared with laboratory-based assays. However, there is a significant gap in our understanding of its human resource impact at the facility level. This study evaluates front-line health workers' (HWs') time associated with EID. Setting: Using time-motion methodology, we collected time-use data on EID tasks performed by HWs at 3 EID facility types in Zimbabwe—5 POC hubs, 9 POC spokes, and 11 facilities that used centralized laboratories. Methods: Data collectors observed 30 EID processes and 30 HWs' provided self-reported time. Comparisons of mean differences of HWs' time-use between centralized and POC EID were performed with a 2-sample t test with unequal variances. Results: Observed average total labor time per EID test at POC facilities was 28 minutes, 22 seconds [95% confidence interval (CI): 22:51 to 35:48], which was equivalent to the average preresult time at facilities using centralized EID. HWs performed other tasks while the machine processed samples. Observed average preresult time (counseling to sample preparation) was 18 minutes, 6 Supported by seconds (95% CI: 13:00 to 23:42) for POC compared with 27 minutes, 48 seconds (95% CI: 23:48 to 32:50) for facilities using centralized laboratories. The mean difference of 9 minutes, 42 seconds (95% CI: 03:04 to 16:18) was statistically significant. The differences in self-reported average total labor time per EID test between HWs at facilities using centralized laboratories or POC were not statistically significant. Conclusion: Use of POC assays did not incur additional human resource time compared with sending dried blood spots to a centralized laboratory for EID.